Comparison of Surface Water‐Groundwater Exchange Fluxes Derived From Hydraulic and Geochemical Methods and a Regional Groundwater Model. Issue 3 (3rd March 2021) - Bouchez, Camille; Cook, Peter G.; Partington, Daniel; Simmons, Craig T.
Abstract: Intercomparison of surface water‐groundwater (SW‐GW) exchange fluxes at the regional scale is rarely undertaken, mainly because estimates are method and scale‐dependent and usually associated with large errors. In the present study, we compare SW‐GW exchange fluxes calculated from a multitracer mass balance in the river, an application of Darcy's law using near‐river piezometers and a surface‐subsurface flow model calibrated at the catchment scale. SW‐GW exchange fluxes are estimated for 7 km long reaches along the 140 km long Campaspe River, a tributary of the Murray River, Australia. Differences are found in the directions and magnitudes of the exchange fluxes estimated by the different methods. The application of Darcy's law in near‐river piezometers seems the most appropriate method to infer SW‐GW flow directions and temporal variability. The tracer mass balance is limited to gaining reaches but gives quantitative estimates of the fluxes. While numerical models should overcome deficiencies associated with some of the intrinsic assumptions of the two field‐methods, the regional‐scale calibration is subject to high uncertainties in the simulated heads near the river, resulting in uncertainty of SW‐GW exchange fluxes. In particular, we show that loosely quantified river abstractions and irrigation patterns directly impact the simulated SW‐GW fluxes. In gaining reaches, additional river chemistry data improved model calibration and SW‐GW flux estimates. While numerical models are crucial for water management, their reliability to estimate SW‐GW fluxes can be limited by their complexity and lacking data availability. Therefore, we recommend comparing numerical model results with easily implemented field‐based methods. Plain Language Summary: Water circulation between surface water and groundwater in watersheds significantly impacts water management, water quality and water availability for aquatic ecosystems. At the regional scale, surface water‐groundwater (SW‐GW) interactions are the result of a number of interaction processes. Despite the growing demand for integrated water studies, the best approach for investigating SW‐GW interactions at large scales remains unclear. We have compared directions and magnitudes of SW‐GW flows estimated from commonly applied local field‐studies and from the implementation of a regional numerical model, along a 140 km river reach in Victoria, Australia. The study highlights the advantages and limitations of each method and suggests the need for a precautionary approach in the use of regional numerical models for estimating SW‐GW fluxes. Field‐based methods are easy to implement and should be used for checking fluxes obtained from numerical models. Key Points: On the regional scale, the surface water‐ground water (SW‐GW) exchange fluxes estimated by three methods differ both in direction and magnitude Flow direction and its temporal variability are indicated by hydraulic heads, tracer mass balance gives flow magnitude in gaining reaches Missing data yield a poor calibration of the regional scale numerical model and erroneous SW‐GW fluxes in losing reaches